Life-death as everyday ritual: theological and socioreligious reflections in times of pandemic - Peretti, Clélia (2022)
We reflect on life-death as everyday ritual in front of COVID-19. In the methodology, we delineate a qualitative, historiobiographical research, which brought together the writings of Edith Stein, Dulce Critelli and Osmair Cândido. We are interested in how German philosophy helps Cândido to face the horrors of the pandemic, such as taking a child’s coffin from its mother ‘s hands or burying twelve people on the same day, ignoring funeral rites. Perpendicular to the wall that appears, another is unveiled, supporting the corpses he has piled up. Cândido sits on the edge of the world, where even God ends.